Combined fused in sarcoma‐positive (FUS+) basophilic inclusion body disease and atypical tauopathy presenting with an amyotrophic lateral sclerosis/motor neurone disease (ALS/MND)‐plus phenotype. (19th February 2019) - Wharton, S. B.; Verber, N. S.; Wagner, B. E.; Highley, J. R.; Fillingham, D. J.; Waller, R.; Strand, K.; Ince, P. G.; Shaw, P. J.
Abstract : Aims: Amyotrophic lateral sclerosis/motor neurone disease (ALS/MND) is characterized by the presence of inclusions containing TDP‐43 within motor neurones. In rare cases, ALS/MND may be associated with inclusions containing other proteins, such as fused in sarcoma (FUS), while motor system pathology may rarely be a feature of other neurodegenerative disorders. We here have investigated the association of FUS and tau pathology. Methods: We report a case with an ALS/MND‐plus clinical syndrome which pathologically demonstrated both FUS pathology and an atypical tauopathy. Results: Clinical motor involvement was predominantly present in the upper motor neurone, and was accompanied by extrapyramidal features and sensory involvement, but with only minimal cognitive impairment. The presentation was sporadic and gene mutation screening was negative. Post mortem study demonstrated inclusions positive for FUS, including basophilic inclusion bodies. This was associated with 4R‐tauopathy, largely as non‐fibrillary diffuse phospho‐tau in neurones, with granulovacuolar degeneration in a more restricted distribution. Double‐staining revealed that neurones contained both types of protein pathology. Conclusion: FUS‐positive basophilic inclusion body disease is a rare cause of ALS/MND, but in this case was associated with an unusual atypical tauopathy. The coexistence of two such rare neuropathologies raises the question of a pathogenic interaction.